Survey da tecnologia MPLS e suas aplicações - Hammerle, Luann Hanns (2013)
MPLS (Multi-Protocol Label Switching) is a technology that has grown in recent years and is still in constant expansion. Increasingly, service providers are migrating their network equipment for this technology. With this technology the implementation of services with quality of service, virtual private networks and traffic engineering is improved. This work will provide a survey on MPLS technology, as well as its main applications. The goal is to help telecommunications professionals to understanding this technology.